The Relationship of Parent Knowledge as Closed Contact about Tuberculosis with Behavior to Prevent Tuberculosis Transmission - Maulana, Nova; Handriyanto, Nova Tri; Yuarsa, Tri Agus; Wisnubroto, Agung Prabowo; Esmayanti, Ratna; Kurnia, Nia Marlina (GLOBAL HEALTH SCIENCE GROUP, 2024)
Pulmonary Tuberculosis is a disease with a very fast transmission rate. The bad impact of tuberculosis infection is death. The increase in pulmonary TB sufferers in Indonesia is caused by unhealthy living behavior and lack of knowledge about the management of precautionary measures for pulmonary tuberculosis transmission. This study aims to determine the relationship between parents' knowledge as close contacts about tuberculosis and behavior to prevent tuberculosis transmission in the Pungkuran Pleret area of Bantul. This quantitative research uses observational research with a cross sectional approach. The population in this study were close contact families of TB sufferers in the Pungkuran Pleret area. The sampling technique used purposive sampling and obtained 30 respondents. Data was collected by checking questionnaires that had been tested as valid and reliable. Meanwhile, the data analysis technique uses the chi-square test. The results of the research can be concluded that the majority of respondents have good knowledge about tuberculosis, 13 respondents (43.34%), but it appears that the majority of respondents still have poor or negative TB prevention behavior, 20 respondents (66.67%). The most cross tabulation results were that there were 10 respondents (33.33%) with the analysis having good knowledge about tuberculosis and having behaved positively in preventing TB. A total of 10 respondents (33.33%) with analysis had insufficient knowledge about tuberculosis and preventive behavior in the negative category. However, in total, the majority of close contact parent respondents in the Pungkuran Pleret area have behavior that is still in the negative category in preventing TB. The results of the chi-square analysis test showed a p-value of 0.000, which means there is a relationship between parents' knowledge as close contacts about tuberculosis and behavior to prevent tuberculosis transmission in the Pungkuran Pleret area.